2021
DOI: 10.1016/j.bsheal.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Finding the real COVID-19 case-fatality rates for SAARC countries

Abstract: The crude case fatality rate (CFR), because of the calculation method, is the most accurate when the pandemic is over since there is a possibility of the delay between disease onset and outcome. Adjusted crude CFR measures can better explain the pandemic situation by improving the CFR estimation. However, no study has thoroughly investigated the COVID-19 adjusted CFR of the SAARC countries. This study estimated both survival interval and underreporting adjusted CFR of COVID-19 for these countries. Moreover, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…As of 16 September 2020, a total of 58,327 cases were reported, and cases reached 268,948 on 22 January 2021 (end of the study) [ 14 ]. Despite a rapid spread of COVID-19, Nepal had high recovery rate, about 98%, as of 22 January 2021 [ 15 ], and a relatively low case fatality rate (CFR); the CFR was 0.6% up to 8 October 2020 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As of 16 September 2020, a total of 58,327 cases were reported, and cases reached 268,948 on 22 January 2021 (end of the study) [ 14 ]. Despite a rapid spread of COVID-19, Nepal had high recovery rate, about 98%, as of 22 January 2021 [ 15 ], and a relatively low case fatality rate (CFR); the CFR was 0.6% up to 8 October 2020 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The case fatality rate in our study population was 1.89% and 1.6% during the first wave and second wave respectively. A study published by Shah et al, found that the CFR for SAARC countries were lower than the developed countries and the estimated crude and adjusted CFR for India was 1.542% and 1.601% (95% CI 1.548 -1.684) during the first wave (Shah et al, 2021). Another study by Bogam et al, estimated that the fatality rate was 12 47% lower in the delta variant driven second wave than in the first wave (adjusted CFR 0.43; 95% CI 0.41 -0.45) (Bogam et al, 2021) despite the large numbers.…”
Section: Discussionmentioning
confidence: 97%
“…Different factors have been studied (younger population, previous exposure to other Coronaviruses that provides immunity, genetic differences, hygiene etiquette, lower infectious load, etc.) without reaching a clear conclusion: probably, having a young population influences, but on the other hand, comorbidities, poverty, frailty malnutrition, and congested urban living may have an adverse effect on risk that may increase both rates ( Ioannidis, 2021 , Shah et al, 2021 ).…”
Section: Case-fatality Rate and Mortalitymentioning
confidence: 99%